MRC5 cells engineered to express ACE2 serve as a model system for the discovery of antivirals targeting SARS-CoV-2 - Uemura, Kentaro; Sasaki, Michihito; Sanaki, Takao; Toba, Shinsuke; Takahashi, Yoshimasa; Orba, Yasuko; Hall, William W.; Maenaka, Katsumi; Sawa, Hirofumi; Sato, Akihiko (Scientific reports, 2021)
Although the spread of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has resulted in a worldwide pandemic, there are currently no virus-specific drugs that are fully effective against SARS-CoV-2. Only a limited number of human-derived cells are capable of supporting SARS-CoV-2 replication and the infectivity of SARS-CoV-2 in these cells remains poor. In contrast, monkey-derived Vero cells are highly susceptibility to infection with SARS-CoV-2, although they are not suitable for the study of antiviral effects by small molecules due to their limited capacity to metabolize drugs compared to human-derived cells. In this study, our goal was to generate a virus-susceptible human cell line that would be useful for the identification and testing of candidate drugs. Towards this end, we stably transfected human lung-derived MRC5 cells with a lentiviral vector encoding angiotensin-converting enzyme 2 (ACE2), the cellular receptor for SARS-CoV-2. Our results revealed that SARS-CoV-2 replicates efficiently in MRC5/ACE2 cells. Furthermore, viral RNA replication and progeny virus production were significantly reduced in response to administration of the replication inhibitor, remdesivir, in MRC5/ACE2 cells compared with Vero cells. We conclude that the MRC5/ACE2 cells will be important in developing specific anti-viral therapeutics and will assist in vaccine development to combat SARS-CoV-2 infections.